Marketing Strategy Of Ayiak Nelengau Food Hotel In Bengkulu Selatan - Arius Mariono; Sri Handayani; Yesi Indian Ariska (Penerbit Jurnal Indonesia, 2021)
Research type which is used in this research proposal is quantitative research with descriptive approach. Analysis method which [is] used in this research is method analyse SWOT (strength, weaknesses, opportunity, threats). obtained datas of research hasail will be analysed by strength, its weakness, its opportunity, and its threat to applying of strategy marketing of Maisonette Eat Ayiak Nelengau. Pursuant to result of analysis of SWOT above obtained that in Internal matrix show strength factor and weakness have totally of score 2,50. This matter of indication that effort from Maisonette of ayiak nelengau reside in internal on course which so strength. Hereinafter, in matrix of ekternal indicate that opportunity factor and threat have totally of score 3,98. This matter of indication that effort from Maisonette of ayiak nelengau earn existing opportunity merespon by remarkable and avoid threat residing in his industrial market. As for strategy able to be recommended by at maisonette of ayiak nelengau is to improve marketing strategy through media social by following progress of technology and also major the quality of product seen purchasing power and also request of consumer.